Faktor Risiko Kejadian Infeksi Saluran Pernapasan Akut Ditinjau dari Kondisi Lingkungan Fisik pada Masyarakat di Kepulauan Spermonde: Penelitian Observasional - Birawida, Agus Bintara; Daud, Anwar; Ibrahim, Erniwati; Sila, Nurlia; Khaer, Ain (Poltekkes Kemenkes Kendari, 2023)
Acute Respiratory Infection (ARI) is a disease caused by the environment and is one of the main causes of high morbidity and mortality. ISPA cases are spread in various areas in South Sulawesi Province, including in the Spermonde Archipelago, Makassar City. In general, there are three main risk factors for the occurrence of ARI, namely environment, individual and behavior. The purpose of this study was to analyze environmental parameters related to the incidence of ARI in the Spermonde Archipelago. The study was conducted using a cross-sectional observational design in 640 neighborhoods. Determination of the sample using the method of proportional systematic random sampling. Statistical data were analyzed by Chi-Square test. The results of the data analysis showed a significant correlation with the variable floor area of ??the house (p = 0.000), indoor lighting (p = 0.023), occupancy density (p = 0.000), and use of mosquito coils (p = 0.000). Variables that did not show a correlation with the incidence of ARI were smoking habits of family members (p = 0.087), ventilation (p = 0.252), and indoor air temperature (p = 0.709). Environmental factors that influence the incidence of ARI are the floor area of ??the house, lighting in the house, residential density, and the use of mosquito coils. Further research is needed to determine the factors causing the physical environmental conditions of the Spermonde Island community.